Islamic Securities Crowdfunding Based on Indonesia's Islamic and Positive Law Perspective - Fahmy, Edian; Zahra, Inas Afifah (CV ODIS, 2023)
This paper analyzes Islamic Securities Crowdfunding (SCF) based on Indonesia's Islamic and positive law perspectives. This paper is a descriptive qualitative by using a normative juridical approach that observes the governing or binding law in society with the convergence on Islamic law and regulations of the Indonesian Financial Services Authority (OJK). The findings reveal that the practice of Islamic SCF is allowed by referring to the Qur'an, Hadith, legal maxim, maqasid al-shariah, and syirkah musahamah contract in DSN-MUI Fatwa No.140/DSN-MUI/VIII/2021 issued on August 24, 2021. Furthermore, from the positive law's perspective, Islamic SCF is allowed to operate by referring to POJK No.57/POJK.04/2020, which accommodates to four principal regulations, namely, organizers, crowdfunding services, issuers, and financiers